Intravenous injection of low-dose flurbiprofen axetil for preventing post-ERCP pancreatitis in high-risk patients: An interim analysis of the trial - Fujita, Yuji; Hasegawa, Sho; Kato, Yuri; Ishii, Ken; Iwasaki, Akito; Sato, Takamitsu; Sekino, Yusuke; Hosono, Kunihiro; Nakajima, Atsushi; Kubota, Kensuke (Endoscopy International Open, 2016)
Background and study aims: Several meta-analyses and randomized control trials have demonstrated the efficacy of rectal nonsteroidal anti-inflammatory drugs for preventing post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Diclofenac or indomethacin was administered at a dose of 100 mg in those studies, which may be too high for Asian population. In addition, rectal administration can be considered complicated.Patients and methods: This study was a prospective, randomized, placebo-controlled trial. Patients with a PEP risk score ≥ 1 were randomly assigned to receive intravenous injection of 50 mg flurbiprofen axetil (flurbiprofen group) or saline only (placebo group). The primary outcome was reduced PEP. The secondary outcome was amylase level after 2 hours of ERCP as a predictor of PEP. (Clinical Trials.gov, ID UMIN000011322)Results: In total, 144 patients were enrolled from August 2013 to March 2015. We performed an interim analysis of the first 100 patients: 47 received flurbiprofen axetil and 53 received placebo. PEP occurred in 11 patients (11 %): 2 of 47 (4.3 %) in the flurbiprofen group and 9 of 53 (17 %) in the placebo group (P = 0.042). Relative risk reduction was 62.4 %. Hyperamylasemia did not differ significantly (17.0 % vs. 26.4 %, P = 0.109). This analysis resulted in early termination of the study for ethical reasons.Conclusions: Intravenous injection of low-dose flurbiprofen axetil after ERCP can reduce the incidence of PEP in high-risk patients